Erosive progression is minimal, but erosion healing rare, in patients with rheumatoid arthritis treated with adalimumab. A 1 year investigator-initiated follow-up study using high-resolution computed tomography as the primary outcome measure. Issue 10 (19th November 2008) - Døhn, U Møller; Boonen, A; Hetland, M L; Hansen, M S; Knudsen, L S; Hansen, A; Madsen, O R; Hasselquist, M; Møller, J M; Østergaard, M
Abstract : Objective: With computed tomography (CT) and radiography, to investigate if repair of bone erosions, defined as regression of erosion scores, occurs during adalimumab treatment of patients with rheumatoid arthritis (RA). Methods: Fifty-two patients with RA, naïve to biological agents, with at least two low-grade radiographic erosions in the wrist or metacarpophalangeal (MCP) joints in the same (index) hand, initiated adalimumab 40 mg subcutaneously every other week. Thirty-five patients completed the study (median age 61 years (interquartile range 46–68), disease duration 8 years (3–15)). CT of the index wrist and MCP joints 2–5 and radiographs of hands and forefeet were obtained at baseline, 6 and 12 months. Images were evaluated by investigators blinded to chronology and clinical data, and assessed according to Sharp/van der Heijde (radiographs) and OMERACT RA MRI scoring (CT) methods. Results: Disease activity score, C-reactive protein, tender and swollen joints count and Health Assessment Questionnaire score had all decreased at 6 and 12 months (wilcoxon signed-ranks test p<0.001). No significant change in any imaging parameters of joint destruction was observed at 6 and 12 months. High intrareader agreements were reached (mean intraobserver intraclass coefficients: 0.96 (CT) and 0.97 (radiography)). The number of patients with change scores exceeding the smallest detectable change (SDC) was comparable on CT and radiography, as were the proportions of patients progressing/regressing. Decreased erosion scores at 12 months were registered in 1.6% and 1.8% of sites assessed on CT and radiography, respectively. Conclusion: Repair of erosions in adalimumab-treated patients with RA is rare, but erosive regression, exceeding the SDC, on CT and radiography occurred. The very limited overall erosive progression supports the view that joint destruction is minimal during adalimumab treatment of patients with RA.